Successful Anesthetic Management for Mandibular Neoplasm Resection in a Patient with Osteogenesis Imperfecta: A Case Report - Indriani, Andi Riza Mirda; T Addi Saputra; Novita Anggraeni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Osteogenesis imperfecta (OI) is a rare genetic disorder characterized by bone fragility and deformities. Patients with mandibular neoplasms and suspected OI require careful anesthetic management to avoid complications. This case report describes the successful anesthetic management of a patient with a mandibular neoplasm and suspected OI. Case presentation: A 33-year-old man presented with a large mandibular tumor causing airway obstruction and difficulty eating. He had physical features suggestive of OI, including short stature, bone deformities, and abnormal tooth growth. Preoperative evaluation revealed a difficult airway due to the tumor and potential cervical spine instability. Anesthesia was induced with propofol and atracurium after securing the airway via ultrasound-guided tracheostomy under local anesthesia. The tumor was resected successfully, and the patient recovered without complications. Conclusion: Anesthetic management in patients with suspected OI and mandibular neoplasms requires careful planning and execution. A multidisciplinary approach, including preoperative evaluation, airway management strategies, and close postoperative monitoring, is crucial for successful outcomes.